2003
DOI: 10.1107/s1600536803000795
|View full text |Cite
|
Sign up to set email alerts
|

L-Valinium hydrogenphosphite

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.003 A Ê Disorder in solvent or counterion R factor = 0.038 wR factor = 0.100 Data-to-parameter ratio = 10.8For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Studies of organic±inorganic hybrid materials, including amino acids and various inorganic acids (Bouchouit et al, 2002;Cherouana et al, 2002;Benali-Cherif, Abouimrane et al, 2002;Bendheif et al, 2003) have received a great deal of attention in recent years because of their electrical, magnetic and optical properties (Kagan et al, 1999;Hill, 1998).…”
Section: Commentmentioning
confidence: 99%
“…Studies of organic±inorganic hybrid materials, including amino acids and various inorganic acids (Bouchouit et al, 2002;Cherouana et al, 2002;Benali-Cherif, Abouimrane et al, 2002;Bendheif et al, 2003) have received a great deal of attention in recent years because of their electrical, magnetic and optical properties (Kagan et al, 1999;Hill, 1998).…”
Section: Commentmentioning
confidence: 99%
“…Phosphites of betainium and glycinium display ferroelectric properties (Fehst et al, 1993;Dacko et al, 1996). There is one more report, on l-valinium phosphite (Bendheif et al, 2003), which was later shown (Fleck & Petrosyan, 2014) to be dl-valinium phosphite.…”
Section: Introductionmentioning
confidence: 97%
“…As observed in 2-amino-5-nitropyridinium hydrogenphosphite (Pecaut & Bagieu-Beucher, 1993), anilinium hydrogenphosphite (Paixã o, Matos Beja, Ramos Silva & Martin-Gil, 2000), 3-ammonium propanoic acid monohydrogenphosphite (Averbuch-Pouchot, 1993b) and diphenylguanidinium monohydrogenphosphite phosphorous-acidwater (Paixã o, Matos Beja, Ramos Silva & Alte da Veiga, 2000), the phosphite groups are hydrogen-bonded in pairs (clusters). In other organic phosphite examples (Averbuch-Pouchot, 1993a,c,d,e;Fleck et al, 2000;Paixã o et al, 2001;Harrison, 2003a,b,c;Mahmoudkhani & Langer, 2001;Harrison, 2004) the phosphite monoanions are linked to form infinite chains, whereas in some organic compounds (Averbuch-Pouchot, 1993f;Idrissi et al, 2002;Bendheif et al, 2003;Gordon & Harrison, 2003) the monoanions are not held together, i.e. no hydrogen bonding occurs between H 2 PO À 3 anions.…”
Section: Introductionmentioning
confidence: 99%